The outburst decay of the low magnetic field magnetar SWIFT J1822.3−1606: phase-resolved analysis and evidence for a variable cyclotron feature. Issue 4 (13th January 2016) - Rodríguez Castillo, Guillermo A.; Israel, Gian Luca; Tiengo, Andrea; Salvetti, David; Turolla, Roberto; Zane, Silvia; Rea, Nanda; Esposito, Paolo; Mereghetti, Sandro; Perna, Rosalba; Stella, Luigi; Pons, José A.; et al.
Abstract: We study the timing and spectral properties of the low-magnetic field, transient magnetar SWIFT J1822.3−1606 as it approached quiescence. We coherently phase-connect the observations over a time-span of ∼500 d since the discovery of SWIFT J1822.3−1606 following the Swift -Burst Alert Telescope (BAT) trigger on 2011 July 14, and carried out a detailed pulse phase spectroscopy along the outburst decay. We follow the spectral evolution of different pulse phase intervals and find a phase and energy-variable spectral feature, which we interpret as proton cyclotron resonant scattering of soft photon from currents circulating in a strong (≳10 14  G) small-scale component of the magnetic field near the neutron star surface, superimposed to the much weaker (∼3 × 10 13  G) magnetic field. We discuss also the implications of the pulse-resolved spectral analysis for the emission regions on the surface of the cooling magnetar.